2007
DOI: 10.1007/s00122-007-0639-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel mitochondrial genome type and development of molecular markers for cytoplasm classification in radish (Raphanus sativus L.)

Abstract: Plant mitochondrial genomes have complex configurations resulting from the multipartite structures and highly rearranged substoichiometric molecules created by repetitive sequences. To expedite the reliable classification of the diverse radish (Raphanus sativus L.) cytoplasmic types, we have developed consistent molecular markers within their complex mitochondrial genomes. orf138, a gene responsible for Ogura male-sterility, was detected in normal cultivars in the form of low-copy-number substoichiometric mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 40 publications
0
27
2
1
Order By: Relevance
“…For instance, restoration of fertility in common bean is related with the suppression of copy number of a substoichiometric CMSassociated ORF by the action of a restorer gene (Janska et al 1998). Recent studies in radish also showed that a CMS-associated ORF exists even in a normal cytoplasm, although the copy number of this ORF is maintained at a very low level (Kim et al 2007b). The substoichiometric copy number of mitochondrial DNA molecules can be stably maintained through generations by unknown mechanisms (Kim et al 2007b).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…For instance, restoration of fertility in common bean is related with the suppression of copy number of a substoichiometric CMSassociated ORF by the action of a restorer gene (Janska et al 1998). Recent studies in radish also showed that a CMS-associated ORF exists even in a normal cytoplasm, although the copy number of this ORF is maintained at a very low level (Kim et al 2007b). The substoichiometric copy number of mitochondrial DNA molecules can be stably maintained through generations by unknown mechanisms (Kim et al 2007b).…”
Section: Introductionmentioning
confidence: 94%
“…Recent studies in radish also showed that a CMS-associated ORF exists even in a normal cytoplasm, although the copy number of this ORF is maintained at a very low level (Kim et al 2007b). The substoichiometric copy number of mitochondrial DNA molecules can be stably maintained through generations by unknown mechanisms (Kim et al 2007b).…”
Section: Introductionmentioning
confidence: 95%
“…Previously, we classified radish germplasm into four cytotypes (DBRMF1, DBRMF2, Ogura and DCGMS) based on polymorphisms of the mitochondrial genome organizations and non-coding chloroplast sequences (Kim et al 2007(Kim et al , 2009aLee et al Fig. 5 Linkage analysis of the Rfo and Rfd1 loci in the backcross population (MS19 9 (MS19 9 R121)).…”
Section: Inheritance Pattern Of Fertility Restoration Of Cms Induced mentioning
confidence: 99%
“…Specific stoichiometry of sublimons is maintained in plants containing the same type of cytoplasm (cytotypes) through many generations (Sakai and Imamura 1993;Bellaoui et al 1998;Janska et al 1998;Kim et al 2007). However, the stoichiometry can be changed by a phenomenon called substoichiometric shifting.…”
Section: Introductionmentioning
confidence: 99%
“…Even the stoichiometry of subgenomes varies at an intraspecific level (Palmer 1988;Allen et al 2007). Specific stoichiometry of subgenomes is maintained through generations, but can be changed by triggers such as tissue culture and nuclear genes (Sakai and Imamura 1993;Bellaoui et al 1998;Janska et al 1998;Kim et al 2007). Nuclear genes controlling stoichiometry of subgenomes such as Msh1 (Abdelnoor et al 2006), RecA (Shedge et al 2007), and OSB1 (Zaegel et al 2006) have been reported.…”
Section: Introductionmentioning
confidence: 99%